Disparitas Pemidanaan Terhadap Pelaku Tindak Pidana Pencurian Dengan Kekerasan Secara Berlanjut - Sutikno, Sutikno (Jurnal Sosial Humaniora Sigli, 2025)
This research aims to analyze disparities in punishment in the qualifications and application of material criminal law for acts of theft with violence and without the right to own sharp weapons in the Central Jakarta District Court Decision Number 208/Pid.B/2024/PN Jkt.Pst., and the District Court Decision Central Jakarta Number 226/Pid.B/2024/PN Jkt.Pst.            This research uses normative legal research methods with a statutory approach and a case approach. As well as using secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. Furthermore, all the material that has been obtained is analyzed in order to answer the problem being researched regarding the disparity in punishment for perpetrators of theft with ongoing violence.            If you pay attention to theft with violence and weighting, it is actually not much different and if you refer to the applicable regulations outlined in the Criminal Code which contains rules regarding all forms of criminal acts, there clearly regulates the differences between the two types of criminal acts of theft above, criminal acts. theft with violence in aggravating circumstances, goods moving from their original place to the desired place, violence against people who have rights. The research method used in this research is a normative juridical approach. Normative juridical is a form of research by looking at library studies or often also called library research, library research or document studies, such as laws, books related to the problem, namely regarding decision letters. The nature of the research in this study is descriptive analysis, namely research that describes criminal procedural law and then compares it with cases. This is intended to provide data as thorough as possible which can help strengthen theories regarding decision letters in the criminal justice process. Theft with violence in aggravating circumstances as regulated in Article 362 and Article 363 of the Criminal Code is a theft that can be qualified and has elements of violence compared to ordinary theft. Keywords : Inclusion, Theft with Violence, Incrimination..